The bookshop of yesterdays [large type] : a novel - Meyerson, Amy (Thorndike Press Large Print, a part of Gale, a Cengage Company, 2018)
Miranda Brooks grew up in the stacks of her eccentric uncle Billy's bookstore, solving the scavenger hunts he created just for her. But on her twelfth birthday, Billy has a falling-out with her mother and disappears from Miranda's life. Sixteen years later, she receives unexpected news: Billy has died and left her Prospero Books, which is teetering on bankruptcy, and one final scavenger hunt. Returning to the bookstore as its owner, Miranda is drawn into a journey through Billy's past -- and the terrible secret that tore her family apart.